O PASSAPORTE DE MATERIAIS DE CONSTRUÇÃO: SOLUÇÃO CIRCULAR EM EDIFICAÇÕES COMO BANCO DE MATERIAIS - Munaro, Mayara; Tavares, Sérgio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The building materials passport is a tool to insert circular economy in buildings. Its purpose is to document and track the circular potential of materials, products and systems, providing information from manufacturing, composition to operation, maintenance and reuse potential. In this article, the passport concept of building materials is presented in the context of the built environment, identifying the main advantages and challenges that this mechanism must provide to promote circular practices in civil construction. The proposal is that materials are identified in a database, removed and reused countless times, maintaining / increasing its residual value. It was emphasized the need for joint action based on political initiatives and regulations that allow and facilitate circular practices in civil construction.